Gender and study discipline-specific differences in the opinion about entrepreneurial aspects: An "ICSB academy" investigation. (31st August 2021) - Ruda, Walter; Keller, Pierre G.; El Tarabishy, Ayman; Ascúa, Rubén
ABSTRACT: This article investigates students' evaluations of perceived entrepreneurial benefits and barriers and their desired university support within a sample of the ICSB academies in 2016 and 2017. The authors highlight differences within these evaluations depending on gender and the students' disciplinary background, drawing on social role theory. In general, the participants of the ICSB academies show high entrepreneurial ambitions; this also holds for the generated subgroups (business/non-business and female/male). The support for our derived hypotheses is in line with our theoretical reasoning, showing differences caused by gender and disciplinary background. As a practical implication, our findings facilitate effective student support of higher education institutions.